Ditriaena romeroi sp. nov. (Coleoptera: Buprestidae), a new species from northwestern Venezuela - Hornburg, Michael; Gottwald, Stephan (Zootaxa, 2012)
Ditriaena (Ditriaena) romeroi sp. nov., from the state of Falcón in northwestern Venezuela, is described, illustrated andcompared with related species. Additional distributional and biological data of other Buprestidae species, collected at the type locality, are given.Se describe Ditriaena (Ditriaena) romeroi sp. nov. del estado Falcón en el noroeste de Venezuela. La especie se ilustra yse compara con especies afines. Además se dan datos adicionales de distribución y biología de otras especies bupréstidos coleccionados en la localidad típica.